Antigen recognition by human γδ T cells: one step closer to knowing. Issue 5 (23rd April 2020) - Eberl, Matthias
Abstract : Sensing of self and non‐self phosphoantigens by human Vγ9/Vδ2 T cells in the context of the butyrophilin family members BTN2A1 and BTN3A1.